The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s00181-015-0920-4
|View full text |Cite
|
Sign up to set email alerts
|

A Markov-switching structural vector autoregressive model of boom and bust in the Australian labour market

Abstract: Major economic events, such as the global financial crisis, are episodes of identifiable duration that differ from other time periods. Using monthly data on the unemployment rate, labour force participation rate and employment for Australia for the period from 1978 to 2012, we estimate a Markov-switching SVAR model to examine the relationship between unemployment and labour force participation and the performance of the Australian labour market. Three distinct labour market regimes are identified. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Gaston and G. Rajaguru (2015) investigated the unemployment rate, the labour force participation rate (LFPR) and the employment rate in Australia during the period from 1978 to 2012. They estimated the Markov-switching structural vector autoregression (SVAR) in order to examine the relationship between unemployment, labour force participation and productivity in the Australian labour market [11]. The research revealed the existence of different regimes in the functioning of the labour market, including the regime with low unemployment and the low Labour Force Participation Rate (LFPR), the long period of relative stability and the short period of high unemployment and a low coefficient of labour force participation.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Gaston and G. Rajaguru (2015) investigated the unemployment rate, the labour force participation rate (LFPR) and the employment rate in Australia during the period from 1978 to 2012. They estimated the Markov-switching structural vector autoregression (SVAR) in order to examine the relationship between unemployment, labour force participation and productivity in the Australian labour market [11]. The research revealed the existence of different regimes in the functioning of the labour market, including the regime with low unemployment and the low Labour Force Participation Rate (LFPR), the long period of relative stability and the short period of high unemployment and a low coefficient of labour force participation.…”
Section: Brief Literature Reviewmentioning
confidence: 99%